2006
DOI: 10.1542/peds.2005-2520
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations and Risk Factors of Children Receiving Triple Ventilating Tube Insertions for Treatment of Recurrent Otitis Media With Effusion

Abstract: The probability of receiving additional ventilating tube insertion because of recurrent otitis media with effusion significantly increased in younger patients at the time of first ventilating tube insertion. The concurrent adenoidectomy, duration of the ventilating tube, postoperative otorrhea within 1 month, and early extrusion of the ventilating tube also influenced the probability of additional ventilating tube insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 19 publications
2
36
1
Order By: Relevance
“…In the present study, male patients were more likely to undergo tympanostomy tube insertion than females, consistent with many of the previous studies. However, sex was not a risk factor for additional tube insertion [4,8]. In our study also sex was not a risk factor for OME recurrence after extrusion of tympanostomy tubes.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…In the present study, male patients were more likely to undergo tympanostomy tube insertion than females, consistent with many of the previous studies. However, sex was not a risk factor for additional tube insertion [4,8]. In our study also sex was not a risk factor for OME recurrence after extrusion of tympanostomy tubes.…”
Section: Discussionsupporting
confidence: 43%
“…In addition the recurrence rate of OME in children was found to be higher at ages from 2 to 5 years than from 7 to 8 years [11]. Ahn et al [4] found that the probability of receiving additional tube insertion due to recurrent OME significantly increased in younger patients at the time of first tympanostomy tube insertion. In another study, being a child younger than 18 months at the time of first tympanostomy tube insertion increased the risk for additional tube insertions [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] The etiology of chronic serous otitis media is multifactorial which includes adenoid hypertrophy, infection (viral or bacterial), allergy, environment and social factors. [3] Geographic and socioeconomic factors such as overcrowding, poor diet and lack of health care may contribute to the development of otitis media. Other risk factors include male gender, bottle feeding and feeding position.…”
mentioning
confidence: 99%